2018
DOI: 10.1136/jnnp-2018-319301
|View full text |Cite
|
Sign up to set email alerts
|

Food allergies are associated with increased disease activity in multiple sclerosis

Abstract: ObjectiveThe association between allergy and multiple sclerosis (MS) is still unclear. In our study, we assessed the association between a self-reported history of allergic conditions with MS clinical and MRI disease activity.MethodsA subset of 1349 patients enrolled in the Comprehensive Longitudinal Investigation of Multiple Sclerosis at the Brigham and Women’s Hospital (CLIMB) study completed a self-administered questionnaire on environmental, food and drug allergies. Patients were distributed among four all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Traditional food allergy tests have revealed connections between food allergies and some CIDs. For instance, a study showed that multiple sclerosis patients with food allergy had greater disease severity than those without food allergy [237], however, conflicting results indicate the need for more research [238]. In a subset of rheumatoid arthritis patients, a study using skin prick testing for food allergy detection [239] found a number of foods that affected symptoms and inflammatory markers.…”
Section: Food Allergies and Hypersensitivitiesmentioning
confidence: 99%
“…Traditional food allergy tests have revealed connections between food allergies and some CIDs. For instance, a study showed that multiple sclerosis patients with food allergy had greater disease severity than those without food allergy [237], however, conflicting results indicate the need for more research [238]. In a subset of rheumatoid arthritis patients, a study using skin prick testing for food allergy detection [239] found a number of foods that affected symptoms and inflammatory markers.…”
Section: Food Allergies and Hypersensitivitiesmentioning
confidence: 99%
“…In their JNNP article, Fakih et al 3 show that patients with MS and self-reported food allergies have more relapses and a higher likelihood of gadolinium-enhancing lesions compared with patients with no known allergies. Using a well-validated cohort from a single centre, 1349 patients with MS were asked about environmental, food and drug allergies.…”
Section: The Evidence On the Association Between Allergies And Multipmentioning
confidence: 99%
“…The CLIMB study evaluated the association between a self-reported history of allergic conditions with the MS clinic and magnetic resonance imaging activity. The rate of the cumulative number of attacks was 1.48 times higher in patients with MS and food allergies compared to unknown allergies, and the probability of having gadolinium-enhanced lesions on magnetic resonance imaging (MRI) was more than twice [ 48 ].…”
Section: Introductionmentioning
confidence: 99%